Investigation of pilots' mental health and analysis of influencing factors in China: based on structural equation model - Feifei Yu; Xuxia Li; Jishun Yang (BMC, 2022)
Abstract Background Pilots' physical and mental health might be significant contributing factors to flight safety. Exploring pilots' health-related quality of life (HRQoL) is crucial for aviation security, health management, and psychological security. This study aimed to explore HRQoL and mental health of pilots and analyze the health characteristics and influencing factors, such as demographic data, personality traits, social support, and resilience. It may provide data for a theoretical basis for aviation security work and health management strategy. Methods This is a cross-sectional study using quantitative approaches. Two hundred twenty male pilots with an average age of 33.31 years participated. They answered a social demographic questionnaire, Symptom Checklist-90, Short Form 36 Health Survey Questionnaire, Perceived social support scale, Connor-Davidson resilience scale, and Big Five Personality Inventories, whose data were analyzed using descriptive and inferential statistics. Results The mediating effect of personality factors between resilience and the HRQoL of pilots was observed. Personality factors also mediated the relationship between social support and the mental health of pilots. Conclusion Pilots' mental health and quality of life need to be taken seriously. Social support, resilience, and personality factors affect pilots' mental health and quality of life.